Serum neurofilament light chain in early relapsing remitting MS is increased and correlates with CSF levels and with MRI measures of disease severity. (October 2016) - Kuhle, Jens; Barro, Christian; Disanto, Giulio; Mathias, Amandine; Soneson, Charlotte; Bonnier, Guillaume; Yaldizli, Özguer; Regeniter, Axel; Derfuss, Tobias; Canales, Mathieu; Schluep, Myriam; Du Pasquier, Renaud; et al.
Background/objectives: Neurofilament light chain (NfL) levels in the cerebrospinal fluid (CSF) of multiple sclerosis (MS) patients correlate with the degree of neuronal injury. To date, little is known about NfL concentrations in the serum of relapsing remitting multiple sclerosis (RRMS) patients and their relationship with CSF levels and magnetic resonance imaging (MRI) measures of disease severity. We aimed to validate the quantification of NfL in serum samples of RRMS, as a biofluid source easily accessible for longitudinal studies. Methods: A total of 31 RRMS patients underwent CSF and serum sampling. After a median time of 3.6 years, 19 of these RRMS patients, 10 newly recruited RRMS patients and 18 healthy controls had a 3T MRI and serum sampling. NfL concentrations were determined by electrochemiluminescence immunoassay. Results: NfL levels in serum were highly correlated to levels in CSF ( r = 0.62, p = 0.0002). Concentrations in serum were higher in patients than in controls at baseline ( p = 0.004) and follow-up ( p = 0.0009) and did not change over time ( p = 0.56). Serum NfL levels correlated with white matter (WM) lesion volume ( r = 0.68, p < 0.0001), mean T1 ( r = 0.40, p = 0.034) and T2* relaxation time ( r = 0.49, p = 0.007) and with magnetization transfer ratio in normal appearing WM ( r = −0.41, p = 0.029). Conclusion: CSF and serum NfL levels were highly correlated, and serum concentrations were increased in RRMS. Serum NfL levels correlated with MRI markers of WM disease severity. Our findings further support longitudinal studies of serum NfL as a potential biomarker of on-going disease progression and as a potential surrogate to quantify effects of neuroprotective drugs in clinical trials.